Effect of soil pH on the establishment of litchi (Litchi chinensis) plants in an alkali environment* - SAXENA, C K; GUPTA, S K (The Indian Journal of Agricultural Sciences, 2011)
A switch over 60m arable to horticultural crops could ensure nutritional security and help to conserve natural resources and boost export through value-addition. Most of the reclaimed alkali lands under rice-wheat system assessed at around 1.3 million ha provide an opportunity to achieve this objective. As the reclamation process of alkali lands proceeds over the years, questions about the suitability of these lands for salt sensitive horticultural crops are being addressed to the research organizations...........